Bidirectional Bend Sensor Employing a Microfiber-Assisted U-Shaped Fabry-Perot Cavity - Zhiyong Bai; Shecheng Gao; Mi Deng; Zhe Zhang; Mingquan Li; Feng Zhang; Changrui Liao; Ying Wang; Yiping Wang (IEEE Photonics Journal)
A bidirectional bend sensor based on U-shaped Fabry-Perot interferometer (UFPI) is experimentally demonstrated. The UFPI is constructed by eccentrically splicing a section of microfiber between two cleaved standard single mode fiber end faces serving as mirrors. A preliminary theoretic analysis of bending response of UFPI is presented. The bend and temperature sensing properties are measured. The theoretical and experimental investigation demonstrates the bending direction discrimination and the monotonous sensing characteristic in a single direction along or opposite to the cavity opening direction. The proposed bend sensor with more compact (∼105 μm in length) and easier fabrication presents a high contrast of the interferometer fringes and low temperature sensitivity of 1.21 × 10 −3 nm/°C.